Composition of the HLA‐DR‐associated human thymus peptidome. Issue 9 (12th July 2013) - Collado, Javier A.; Alvarez, Iñaki; Ciudad, M. Teresa; Espinosa, Gabriel; Canals, Francesc; Pujol‐Borrell, Ricardo; Carrascal, Montserrat; Abian, Joaquín; Jaraquemada, Dolores
<x xml:space="preserve">Abstract</x> Major histocompatibility complex class II (MHC‐II) molecules bind to and display antigenic peptides on the surface of antigen‐presenting cells (APCs). In the absence of infection, MHC‐II molecules on APCs present self‐peptides and interact with CD4+ T cells to maintain tolerance and homeostasis. In the thymus, self‐peptides bind to MHC‐II molecules expressed by defined populations of APCs specialised for the different steps of T‐cell selection. Cortical epithelial cells present peptides for positive selection, whereas medullary epithelial cells and dendritic cells are responsible for peptide presentation for negative selection. However, few data are available on the peptides presented by MHC molecules in the thymus. Here, we apply mass spectrometry to analyse and identify MHC‐II‐associated peptides from five fresh human thymus samples. The data show a diverse self‐peptide repertoire, mostly consisting of predicted MHC‐II high binders. Despite technical limitations preventing single cell population analyses of peptides, these data constitute the first direct assessment of the HLA‐II‐bound peptidome and provide insight into how this peptidome is generated and how it drives T‐cell repertoire formation.